Pancreatoduodenectomy with venous resection for ductal adenocarcinoma rarely achieves complete (R0) resection. Issue 1 (January 2020) - Kleive, Dyre; Labori, Knut J.; Line, Pål-Dag; Gladhaug, Ivar P.; Verbeke, Caroline S.
Abstract: Background: Pancreatoduodenectomy with venous resection is considered standard of care for patients with tumour involvement of the superior mesenteric/portal vein (SMV/PV) and deemed justified if an R0-resection can be achieved. The aim of this study was to provide a detailed pathology assessment of the site and extent of margin involvement in specimens resulting from pancreatoduodenectomy with venous resection. Methods: Retrospective observational study including patients undergoing pancreatoduodenectomy with or without venous resection for pancreatic ductal adenocarcinoma between 2015 and 2017. Detailed histopathological mapping of the tumour and its relationship to the margins was undertaken. Results: 98 patients met the inclusion criteria. An R0-resection, based on 1 mm clearance, was achieved in 16 of 73 patients without venous resection and in 1 of 25 patients with venous resection ( p  = 0.063). The surface of the SMV-groove was the most frequently involved margin (23 of 25 patients with venous resection, 37 of 73 patients without venous resection; p  < 0.001). The broad invasive tumour front as well as the absence of peripancreatic fat at the SMV-groove were the reasons for these findings. Conlusion: An R0-resection following pancreatoduodenectomy with venous resection for ductal adenocarcinoma can rarely be achieved due to microscopical involvement of the SMV-groove.